-4n+2+3n=8-n+6

Simple and best practice solution for -4n+2+3n=8-n+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n+2+3n=8-n+6 equation:


Simplifying
-4n + 2 + 3n = 8 + -1n + 6

Reorder the terms:
2 + -4n + 3n = 8 + -1n + 6

Combine like terms: -4n + 3n = -1n
2 + -1n = 8 + -1n + 6

Reorder the terms:
2 + -1n = 8 + 6 + -1n

Combine like terms: 8 + 6 = 14
2 + -1n = 14 + -1n

Add 'n' to each side of the equation.
2 + -1n + n = 14 + -1n + n

Combine like terms: -1n + n = 0
2 + 0 = 14 + -1n + n
2 = 14 + -1n + n

Combine like terms: -1n + n = 0
2 = 14 + 0
2 = 14

Solving
2 = 14

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5/12+5/12 | | 2x-1/2(3x-2)=7/4-x | | 0=18x^2 | | X-22=15 | | -6-8=9x+7-8x | | -x^2-23x-60=0 | | 17/19+1/19 | | w/4=13 | | -3+21=m-8 | | x*2-0.2x*4x-2400=0 | | 4x-8=5x-2(x+2) | | f(1.8)=2x*x-16x+63 | | x/x+4 | | 1/x+4 | | x-4/x-16 | | f(1.8)=2x*2x-16x+63 | | y/8=17 | | (x-9)(2x^2+x-3)= | | 5/12+1/2 | | 9y-12y=-10-14 | | .24y-4=.14y+2-.7y | | 1/15+3/5 | | 2/5+9/20 | | 8x-4=-29+3x | | x^4+81=18x^2 | | 8t+(3t-4t)= | | 9n-3y=-3 | | -11r-(5-6r)=-(6-3r)+1 | | 3x-7y=-15 | | 13/4(3x+3/4) | | 8(3x+2)/5=x+3 | | 3x-2x+6-1=4x+2 |

Equations solver categories